Polyamide resin composition

The polyamide resin composition, featuring a polyamide resin, polyolefin-based graft copolymer, compatibilizer, and fiber-like filler, addresses the challenges of sliding, heat resistance, and mechanical properties in polyamide resin compositions, resulting in enhanced performance and processability.

JP2025050432APending Publication Date: 2025-04-04ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023159227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing polyamide resin compositions face challenges in achieving excellent sliding properties, heat resistance, and mechanical properties due to issues with the dispersion of fluororesins and polyolefin resins, which can lead to decreased mechanical strength and inconsistent morphological states.

Method used

A polyamide resin composition is developed, comprising a polyamide resin, a polyolefin-based graft copolymer with an aromatic ring in its side chain, a compatibilizer with an olefin or aromatic ring backbone, and a fiber-like filler. This composition is designed to improve compatibility and dispersion, enhancing sliding and mechanical properties.

Benefits of technology

The composition achieves excellent sliding properties, heat resistance, and mechanical properties, including improved abrasion resistance and strength, while maintaining processability and flowability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050432000001
    Figure 2025050432000001
  • Figure 2025050432000002
    Figure 2025050432000002
  • Figure 2025050432000003
    Figure 2025050432000003
Patent Text Reader

Abstract

To provide a polyamide resin composition having improved slidable characteristics and mechanical characteristics.SOLUTION: A polyamide resin composition includes: (A) a polyamide resin; (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer on a side chain thereof; (C) a compatibility accelerator; and (D) a fibrous filler.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide resin composition. [Background technology]

[0002] Polyamide resins are excellent in sliding properties, moldability, mechanical properties, chemical resistance, etc. Polyamide resins have been widely used as parts materials for industrial materials, automobiles, electrical and electronic equipment, and other industrial applications.

[0003] In recent years, metal components have been increasingly replaced with resins in the fields of automobiles, electrical and electronics, and the like. In particular, in the field of automobiles, there is a demand for molding materials that are superior in sliding properties and heat resistance as well as in mechanical properties such as strength and elastic modulus from the standpoint of weight reduction for improved fuel efficiency, cost reduction, and streamlining of assembly processes.

[0004] As a method for further improving the sliding properties of polyamide resin, a technique is known in which a solid lubricant such as a fluorine-based resin, graphite, or molybdenum disulfide is blended with the polyamide resin and kneaded.

[0005] For example, Patent Documents 2 to 4 disclose polyamide resin compositions in which a fluorine-based resin is blended with a polyamide resin to improve the sliding properties. Moreover, Patent Document 1 discloses a sliding member for a power transmission guide obtained by dispersing a polyolefin resin in a polyamide resin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-117842 A [Patent Document 2] International Publication No. WO2013 / 047625 [Patent Document 3] JP 2011-84679 A [Patent Document 4] JP 2012-102189 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the techniques of blending a fluororesin with a polyamide resin as disclosed in Patent Documents 2 to 4, for example, polytetrafluoroethylene is used as the fluororesin to be blended. However, when polytetrafluoroethylene is used as the fluorine-based resin, in order to finely disperse the polytetrafluoroethylene, it is necessary to melt-knead the polytetrafluoroethylene under high shear conditions at a temperature equal to or higher than the melting point of the polytetrafluoroethylene. As a result of the melt-kneading, the polyamide resin deteriorates, resulting in a problem of reduced mechanical strength.

[0008] In addition, in the technology of blending a polyamide resin with a polyolefin resin as disclosed in Patent Document 1, the melt viscosities of the polyamide resin and the polyolefin resin are different, and the melt viscosities of the polyamide resin and the polyolefin resin may change significantly depending on the shear rate applied during production. As a result, there is a problem that the morphology state of the polyolefin resin has a large effect on the mechanical properties and the sliding properties.

[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a polyamide resin composition which is excellent in sliding properties, heat resistance and mechanical properties. [Means for solving the problem]

[0010] The present invention includes the following aspects. [1] (A) a polyamide resin; (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain; (C) a compatibilizer; and (D) a fibrous filler; A polyamide resin composition comprising: [2] The polyamide resin composition according to [1], wherein the (C) compatibilizer has an olefin skeleton and / or an aromatic ring skeleton. [3] The polyamide resin composition according to [1] or [2], characterized in that the content of the (B) polyolefin-based graft copolymer is 1 to 15 parts by mass relative to 100 parts by mass of the (A) polyamide resin, the content of the (C) compatibilizer is 0.01 to 15 parts by mass relative to 100 parts by mass of the (A) polyamide resin, and the content of the (D) fibrous filler is 1 to 150 parts by mass relative to 100 parts by mass of the (A) polyamide resin. [4] The polyamide resin composition according to any one of [1] to [3], wherein the (C) compatibilizer has affinity with an olefin skeleton. [5] The polyamide resin composition according to any one of [1] to [4], wherein the (C) compatibilizer has affinity for aromatic rings. [6] The polyamide resin composition according to any one of [1] to [5], wherein the (C) compatibilizer has a functional group reactive with the (A) polyamide resin. [7] The polyamide resin composition according to any one of [1] to [6], wherein the (B) polyolefin-based graft copolymer has polyethylene in its main chain. [8] The polyamide resin composition according to any one of [1] to [7], wherein the (C) compatibilizer contains a structural unit derived from a carboxylic acid anhydride. [9] The polyamide resin composition according to any one of [1] to [8], wherein the (D) fibrous filler has a ratio (L / d1) of an average major axis L to an average minor axis d1 of 1000 or less.

[10] The polyamide resin composition according to any one of [1] to [9], wherein the (C) compatibilizer has an amide bond in a side chain.

[11] A method for producing a polyamide resin composition, comprising melt-kneading (A) a polyamide resin, (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer in the side chain, and (C) a compatibilizer.

[12] A molded article obtained by molding the polyamide resin composition according to any one of [1] to

[10] .

[13] A sliding member, comprising the polyamide resin composition according to any one of [1] to

[10] . Effect of the Invention

[0011] According to the present invention, it is possible to obtain a polyamide resin composition having excellent sliding properties, heat resistance and mechanical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of the gist thereof.

[0013] In this specification, the term "polyamide" refers to a polymer having an amide (-NHCO-) ​​group in the main chain. Regarding a numerical range, "A or more and B or less" may be expressed as "A to B." For example, "1 to 10 parts by mass" means a numerical range from 1 part by mass to 10 parts by mass, including the lower limit (1 part by mass) and the upper limit (10 parts by mass), that is, "1 part by mass or more and 10 parts by mass or less."

[0014] <Polyamide resin composition> The polyamide resin composition of the present embodiment is a polyamide resin composition containing (A) a polyamide resin (hereinafter, may be referred to as component (A)), (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer in its side chain (hereinafter, may be referred to as component (B)), (C) a compatibilizer (hereinafter, may be referred to as component (C)), and (D) a fibrous filler.

[0015] Hereinafter, each component of the polyamide resin composition of the present embodiment will be described.

[0016] ((A) Polyamide resin) The polyamide resin (A) in the present embodiment is not limited to the following, and examples thereof include (a-1) polyamide obtained by ring-opening polymerization of lactam, (a-2) polyamide obtained by self-condensation of ω-aminocarboxylic acid, (a-3) polyamide obtained by condensation of diamine and dicarboxylic acid, and copolymers thereof.

[0017] As the (A) polyamide resin, only one of the above polyamides may be used alone, or two or more of them may be used as a mixture.

[0018] Here, the lactam used in the production of the polyamide (a-1) includes, but is not limited to, pyrrolidone, caprolactam, undecalactam, dodecalactam, and the like.

[0019] The ω-aminocarboxylic acid used in the production of the polyamide (a-2) is not limited to the following, but examples thereof include ω-amino fatty acids which are ring-opening compounds of the above-mentioned lactams with water. Furthermore, two or more kinds of the lactam or ω-aminocarboxylic acid may be used in combination and condensed.

[0020] The diamine (monomer) used in the production of the (a-3) polyamide is not limited to the following, but examples thereof include linear aliphatic diamines, branched aliphatic diamines, alicyclic diamines, and aromatic diamines.

[0021] The linear aliphatic diamine is not limited to the following, but examples thereof include hexamethylenediamine and pentamethylenediamine. The branched aliphatic diamine is not limited to the following, but examples thereof include 2-methylpentanediamine and 2-ethylhexamethylenediamine. The alicyclic diamine is not limited to the following, but examples thereof include cyclohexanediamine, cyclopentanediamine, and cyclooctanediamine. The aromatic diamine is not limited to the following, but examples thereof include p-phenylenediamine and m-phenylenediamine.

[0022] The dicarboxylic acid (monomer) used in the production of the polyamide (a-3) is not limited to the following, but examples thereof include aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.

[0023] Examples of the aliphatic dicarboxylic acid include, but are not limited to, adipic acid, pimelic acid, and sebacic acid. The alicyclic dicarboxylic acid is not limited to the following, but may be, for example, cyclohexanedicarboxylic acid. The aromatic dicarboxylic acid is not limited to the following, but examples thereof include phthalic acid and isophthalic acid.

[0024] The diamine and dicarboxylic acid as the monomers may be condensed either alone or in combination of two or more kinds.

[0025] The polyamide of the component (A) is not limited to the following, but examples thereof include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecane amide), polyamide 12 (polydodecanamide), polyamide 46 (polytetramethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecamide), polyamide 6T (polyhexamethylene sebac ... Examples of polyamides that can be used include polyamide 9T (polynonamethylene terephthalamide), polyamide 6I (polyhexamethylene isophthalamide), polyamide 2Me5T (poly-2-methylpentamethylene terephthalamide (hereinafter, the methyl group may be abbreviated as Me)), polyamide MXD6 (polymetaxylylene adipamide), and polyamide PXD12 (polyparaxylylene dodecamide), as well as copolymer polyamides containing at least one of these as a constituent component.

[0026] From the viewpoint of improving sliding properties, the (A) polyamide resin is preferably a polyamide resin mainly composed of polyamide 66, polyamide 46, polyamide 4T, polyamide 6T, polyamide 9T, or polyamide 6. The term "main component" used here means a polyamide resin component whose content is 50% by mass or more relative to the total mass of the (A) polyamide resin.

[0027] From the viewpoint of improving heat resistance, the (A) polyamide resin is preferably a polyamide resin mainly composed of polyamide 66, polyamide 46, polyamide 4T, polyamide 6T, polyamide 9T, or polyamide PXD12, and more preferably a polyamide resin mainly composed of polyamide 66.

[0028] The (A) polyamide resin has a relative sulfuric acid viscosity of preferably 2.0 or more, more preferably 2.1 or more, even more preferably 2.3 or more, and particularly preferably 3.2 or more. Furthermore, the relative viscosity in sulfuric acid of the (A) polyamide resin is preferably 4.5 or less, more preferably 4.4 or less, and particularly preferably 4.3 or less.

[0029] When the (A) polyamide resin has a relative viscosity in sulfuric acid of 2.0 or more, a polyamide resin composition having better mechanical properties tends to be obtained. When the (A) polyamide resin has a relative viscosity in sulfuric acid of 4.5 or less, a polyamide resin composition having better flowability and processability tends to be obtained. The sulfuric acid relative viscosity of the polyamide resin (A) can be measured by the method specified in JIS-K6920 shown in the examples described later.

[0030] In the polyamide resin composition of the present embodiment, the component (A) may be a known product, or a commercially available product.

[0031] ((B) Polyolefin-based graft copolymer having aromatic ring-containing polymer in the side chain) The polyamide resin composition in this embodiment contains (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer in a side chain. The (B) polyolefin-based graft copolymer having an aromatic ring-containing polymer in a side chain is not particularly limited as long as it is a polyolefin-based graft copolymer having an aromatic group in a side chain. By including the component (B), the sliding properties of the resulting polyamide resin composition are improved.

[0032] The component (B) is preferably (b-1) an olefin-based graft polymer having polystyrene in the aromatic ring, and more preferably (b-2) an olefin-based graft copolymer having polyethylene in the main chain. The side chain is not limited to polystyrene, and may be a vinyl-based copolymer, etc.

[0033] The method for preparing the component (B) is not particularly limited, and the component (B) can be easily prepared by a known radical reaction. The component (B) can be prepared, for example, by adding a radical catalyst to a monomer constituting an olefin polymer component containing polyethylene and a monomer constituting a vinyl polymer, followed by kneading and grafting. Also included is a method in which a radical catalyst such as a peroxide is added to an olefin polymer component or a vinyl polymer component to generate free radicals, and the generated free radicals are melt-kneaded with the other polymer component to perform grafting.

[0034] The component (B) is a graft copolymer having a polyolefin main chain and an aromatic ring polymer in a side chain, which prevents the component (B) from falling off from the polyamide resin, and allows a polyamide resin composition to be obtained that is excellent in sliding properties, particularly wear resistance.

[0035] The polyamide resin composition of the present embodiment preferably contains at least 50% by mass or more of polyethylene relative to 100% by mass of the component (B).

[0036] The ratio of the olefin polymer (b1) and the vinyl polymer (b2) constituting the component (B) is preferably b1:b2=80:20 to 20:80 (mass ratio), and particularly preferably b1:b2=60:40 to 40:60. By satisfying the above ratio, the sliding properties of the obtained polyamide resin composition can be improved.

[0037] The vinyl copolymer (b2) exhibits high rigidity due to a high glass transition temperature that is a characteristic of an aromatic ring. In addition, the vinyl copolymer prevents the component (B) from easily burning and fusing to the sliding portion of the mating material or the material itself on the sliding surface, which is caused by the temperature of the sliding surface rising due to the frictional force (frictional heat) applied to the sliding surface of the vinyl copolymer. As a result, the sliding characteristics are maintained for a long period of time, and in particular the wear resistance is improved.

[0038] The content of the component (B) in the polyamide resin composition of the present embodiment is preferably 1 to 15 mass %, more preferably 2 to 12 mass %, and further preferably 3 to 10 mass %, relative to 100 mass % of the polyamide resin (A). When the content of the (B) component is equal to or greater than the lower limit (1% by mass), the sliding properties of the resulting polyamide resin composition are effectively exhibited, whereas when the content of the (B) component is equal to or less than the upper limit (15% by mass), the wear resistance and mechanical properties of the resulting polyamide resin composition are improved.

[0039] The component (B) in the polyamide resin composition of the present embodiment may be any known polyolefin graft copolymer having an aromatic side chain, and a commercially available product may also be used.

[0040] ((C) Compatibilizer) The polyamide resin composition in the present embodiment contains a compatibilizer (C). The compatibilizer (C) is not limited to the following, but is not particularly limited as long as it is a compound that can improve the compatibility between a compound containing an olefin skeleton and / or an aromatic ring skeleton and a polyamide resin from the viewpoint of further improving sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc. By blending (C) a compatibilizer for improving the compatibility between the (A) polyamide resin and the (B) polyolefin-based graft copolymer having an aromatic ring-containing polymer in its side chain, the sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, and processability of the polyamide resin composition in this embodiment are further improved.

[0041] The component (C) preferably contains an olefin skeleton and / or an aromatic ring skeleton. The component (C) is preferably a compound capable of improving compatibility with polyamide resins, and is not limited to the following. For example, the component (C) preferably uses at least one product selected from compounds having amide bonds such as polyamides and / or their copolymers, reactive functional groups capable of reacting with terminal groups and / or main chain amide groups of polyamide resins.

[0042] The compound containing the olefin skeleton may be, but is not limited to, at least one product selected from low density polyethylene (LDPE), high density polyethylene (HDPE), low density linear polyethylene (LLDPE), ultra-high molecular weight polyethylene (UHMWPE), very low density polyethylene (VLDPE) obtained by metallocene catalysis, polyethylene, alpha olefin, diolefin, styrene / butadiene / styrene block copolymer (SBS), its hydrogenated product styrene / ethylene-butylene / styrene block copolymer (SEBS), styrene / butadiene copolymer (SBR), its hydrogenated product styrene / ethylene / butylene copolymer (HSBR), styrene / isoprene / styrene block copolymer (SIS), its hydrogenated product styrene / ethylene-propylene / styrene block copolymer (SEPS), etc. In this specification, the olefin skeleton is defined as a compound composed only of carbon atoms and hydrogen atoms.

[0043] Examples of compounds containing an aromatic ring skeleton include, but are not limited to, low-density polyethylene (LDPE), high-density polyethylene (HDPE), low-density linear polyethylene (LLDPE), very low-density polyethylene (VLDPE) obtained by metallocene catalysis, polyethylene, alpha-olefins and diolefins, polystyrene having an aromatic ring skeleton, phenylene ether, modified polyphenylene ether, styrene / butadiene / styrene block copolymer (SBS), its hydrogenated product styrene / ethylene-butylene / styrene block copolymer (SEBS), styrene / butadiene copolymer (SBR), its hydrogenated product styrene / ethylene / butylene copolymer (HSBR), styrene / isoprene / styrene block copolymer (SIS), its hydrogenated product styrene / ethylene-propylene / styrene block copolymer (SEPS), and the like.

[0044] Examples of the alpha olefin include, but are not limited to, ethylene, propylene, butene-1, octene-1, butadiene, and the like. The diolefin is not limited to the following, but examples thereof include diolefin homopolymers and copolymers.

[0045] The (C) compatibilizer preferably has an olefin skeleton and / or an aromatic ring skeleton, although not limited thereto. Furthermore, the (C) compatibilizer preferably has an olefin skeleton and / or an aromatic ring skeleton in the main chain, more preferably has an olefin skeleton and / or a styrene skeleton in the main chain of the (C) component, and particularly preferably has at least an olefin skeleton in the main chain of the (C) component.

[0046] The compound capable of improving the compatibility with the polyamide resin is not limited to the following, but at least one selected from the group consisting of compounds having an amide bond such as polyamide, copolymers containing polyamide, and combinations thereof; compounds having a reactive functional group capable of reacting with an amide group in the terminal group and / or main chain of the polyamide resin; and the like can be used.

[0047] Examples of reactive functional groups capable of reacting with the terminal groups and / or amide groups in the main chain of a polyamide resin include carboxy groups, acid anhydride groups, epoxy groups, oxazoline groups, amino groups, isocyanate groups, maleic acid, itaconic acid, citraconic acid, allylsuccinic acid, cyclohex-4-ene-1,2-dicarboxylic acid, 4-methylenecyclohex-4-ene-1,2-dicarboxylic acid, bicyclo(2,2,1)hept-5-anhydride 2,3-dicarboxylic acid, x-methylbicyclo(2,2,1)hept-5-ene-2,2-dicarboxylic acid, alkyl(methacrylate)acrylates (methyl acrylates), and the like.

[0048] The method for introducing the reactive functional group is not particularly limited, and examples thereof include a method in which a compound having the reactive functional group is reacted in the process for producing the above-mentioned polymer, a method in which the above-mentioned polymer pellets and the compound having the above-mentioned reactive functional group are mixed, kneaded in an extruder, etc., and reacted.

[0049] The (C) compatibilizer is not limited to the following, but is more preferably a compound having an amide bond, such as polyamide and / or a copolymer thereof; or a compound containing a reactive functional group having a structural unit derived from a carboxylic acid anhydride. More preferably, the (C) compatibilizer is a compound having an amide bond and / or a compound having a structural unit derived from maleic acid. Particularly preferably, the (C) compatibilizer is a compound having an amide bond. Most preferably, the (C) compatibilizer is a compound having an amide bond in the side chain.

[0050] In addition, from the viewpoint of achieving even better sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, and the like, the (C) compatibilizer preferably has an olefin skeleton and / or an aromatic ring skeleton; a compound having an amide bond, such as a polyamide and / or a copolymer thereof; or a reactive functional group having a structural unit derived from a carboxylic acid anhydride, although this is not limited to the following. Furthermore, it is more preferable that the (C) compatibilizer has an olefin skeleton and / or an aromatic ring skeleton in the main chain; or contains a compound having an amide bond and / or a structural unit derived from maleic acid. Furthermore, it is particularly preferable that the (C) compatibilizer has only an olefin skeleton or a styrene skeleton in the main chain and an amide bond in the side chain, and it is most preferable that the (C) compatibilizer has an olefin skeleton in the main chain and an amide bond.

[0051] As described above, from the viewpoint of achieving even better sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, and the like, it is most preferable that the (C) compatibilizer is a graft copolymer having an olefin skeleton in the main chain and an amide bond in the side chain. In this case, although not limited thereto, it can be obtained by reacting a residue of an unsaturated monomer in the main chain portion with the end of a skeleton having an amide bond. Examples of the unsaturated monomer include unsaturated epoxides and unsaturated carboxylic acid anhydrides.

[0052] Examples of the unsaturated carboxylic acid anhydride include, but are not limited to, maleic acid, itaconic acid, citraconic acid, allylsuccinic acid, cyclohex-4-ene-1,2-dicarboxylic acid, 4-methylenecyclohex-4-ene-1,2-dicarboxylic acid, bicyclo(2,2,1)hept-5-anhydride 2,3-dicarboxylic acid, and x-methylbicyclo(2,2,1)hept-5-ene-2,2-dicarboxylic acid. The salts and esters of the unsaturated carboxylic acids are not limited to the following, but examples thereof include alkyl (methacrylate) acrylates (methyl acrylate) and the like. The vinyl ester of the saturated carboxylic acid is not limited to the following, but may be, for example, vinyl acetate.

[0053] In the polyamide resin composition of the present embodiment, at least one of the component (B) and the component (C) is a graft copolymer having an olefin skeleton in the main chain and an amide bond in the side chain, and therefore, the composition can exhibit innovative effects not available in known technologies in terms of sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, and the like.

[0054] In addition, from the viewpoint of further improving the compatibility between the olefin skeleton and / or the aromatic ring skeleton and the polyamide resin (A), it is particularly preferable that both of the components (B) and (C) are graft copolymers, although this is not limited thereto.

[0055] In the polyamide resin composition of the present embodiment, the component (C) may be a known product, or a commercially available product.

[0056] The component (C) is not particularly limited, and can also be produced using a masterbatch prepared in advance by melt-kneading at least one compound selected from reactive functional groups capable of reacting with terminal groups of a polyamide resin and / or amide groups in the main chain, and a polymer having an olefin skeleton and / or an aromatic ring skeleton (for example, a thermoplastic resin such as a polyamide resin).

[0057] The component (C) can be produced, for example, by using a masterbatch prepared in advance by melt-kneading a compound having at least one selected from reactive functional groups capable of reacting with an end group and / or an amide group in the main chain of the polyamide resin (A) and a compound having at least one selected from the group consisting of an olefin skeleton and an aromatic ring skeleton (for example, a thermoplastic resin such as a polyamide resin).

[0058] Alternatively, the component (C) may be, for example, a master batch prepared in advance by melt-kneading a precursor of a graft copolymer having an unsaturated monomer in the skeleton and a thermoplastic resin having a functional group reactive with the unsaturated monomer.

[0059] Alternatively, when producing the polyamide resin composition of this embodiment, when the (A) component and the (B) component are melt-kneaded, a graft copolymer precursor having an unsaturated monomer in the skeleton can be blended and reacted with the (A) component to obtain the (C) component. In other words, a polyamide resin composition containing the (A) component, the (B) component, and the (C) component can be obtained by melt-kneading a composition containing the (A) component and the (B) component using an extruder or the like.

[0060] The content of the (C) component in the polyamide resin composition of the present embodiment is preferably 0.01 to 15 parts by mass, more preferably 0.05 to 15 parts by mass, even more preferably 0.1 to 12 parts by mass, and particularly preferably 0.2 to 10 parts by mass, relative to 100 parts by mass of the (A) polyamide resin. When the content of the (C) component is at least the lower limit (0.01 parts by mass), the sliding properties, moldability, processability, etc. are effectively exhibited, and when the content of the (C) component is no more than the upper limit (15 parts by mass), the sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc. are improved.

[0061] (D) Fibrous filler The polyamide resin composition in this embodiment contains (D) a fibrous filler, which may be, but is not limited to, glass fiber, carbon fiber, aramid fiber, cellulose nanofiber, stainless steel fiber, aluminum fiber, brass fiber or other metal fiber, liquid crystal polyester fiber, gypsum fiber, ceramic fiber, asbestos fiber, zirconia fiber, alumina fiber, silica fiber, titanium oxide fiber, silicon carbide fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, milled fiber, etc. These (D) fibrous fillers may be used alone or in combination of two or more kinds.

[0062] Among the above, the (D) fibrous filler is preferably at least one selected from the group consisting of glass fiber, carbon fiber, aramid fiber, cellulose nanofiber, and liquid crystalline polyester fiber, from the viewpoints of sliding properties, heat resistance, rigidity, strength, and the like. From the same viewpoint, the (D) fibrous filler is more preferably one or more selected from the group consisting of glass fiber, carbon fiber, aramid fiber, and cellulose nanofiber, and is further preferably glass fiber and / or carbon fiber.

[0063] When the (D) fibrous filler is glass fiber or carbon fiber, the number average fiber diameter (d1) is preferably 3 μm or more and 30 μm or less. The weight average fiber length (L) is preferably 100 μm or more and 5 mm or less. Furthermore, the aspect ratio ((L) / (d1)) of the number average fiber diameter (d1) to the weight average fiber length (L) is preferably 1000 or less. The aspect ratio ((L) / (d1)) of the number average fiber diameter (d1) to the weight average fiber length (L) is more preferably 3 or more and 100 or less. By using glass fiber or carbon fiber having the above configuration, a higher effect can be achieved.

[0064] When the (D) fibrous filler is glass fiber, the number average fiber diameter (d1) is preferably 3 μm or more and 30 μm or less, the weight average fiber length (L) is preferably 50 μm or more and 5 mm or less, and the aspect ratio ((L) / (d1)) is preferably 3 or more and 100 or less.

[0065] Furthermore, when the (D) fibrous filler is carbon fiber, for example, either polyacrylonitrile (PAN)-based carbon fiber or pitch-based carbon fiber can be used. From the viewpoint of mechanical properties, it is preferable to use PAN-based carbon fiber.

[0066] The above-mentioned fibrous fillers may be used alone or in combination of two or more.

[0067] From the viewpoint of productivity, it is preferable that the carbon fibers as the (D) fibrous filler are added by melt kneading short carbon fibers of about 3 mm to 10 mm in length in an extruder. In this case, it is preferable to add the carbon fibers from a side feeder from the viewpoint of preventing breakage of the carbon fibers.

[0068] From the viewpoint of affinity with polyamide resin, the carbon fibers are preferably coated with a urethane-based sizing agent, a maleic anhydride-based sizing agent, an acrylic-based sizing agent, or a polyamide-based sizing agent. Furthermore, from the viewpoints of physical properties and sliding properties, the carbon fibers preferably have a diameter of 3 μm or more and 10 μm or less.

[0069] The number average fiber diameter and weight average fiber length of the (D) fibrous filler can be measured by the following method. First, the molded product is dissolved in a solvent in which (A) polyamide is soluble, such as formic acid. Next, from the resulting insoluble components, for example, 100 or more (D) fibrous fillers are arbitrarily selected. Next, the (D) fibrous fillers are observed with an optical microscope, a scanning electron microscope, or the like, and the number average fiber diameter can be obtained by dividing the total measured fiber diameter by the number of (D) fibrous fillers measured. Alternatively, the weight average fiber length can be obtained by dividing the total measured fiber length by the total weight of the (D) fibrous fillers measured.

[0070] In the polyamide composition of this embodiment, the content of the (D) fibrous filler is preferably 1 part by mass or more and 150 parts by mass or less, more preferably 3 parts by mass or more and 140 parts by mass or less, even more preferably 5 parts by mass or more and 135 parts by mass or less, particularly preferably 7 parts by mass or more and 130 parts by mass or less, and most preferably 10 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the (A) polyamide. When the content of the (D) fibrous filler is equal to or greater than the lower limit (1 part by mass), the mechanical properties such as strength and rigidity, and the sliding properties of the molded article tend to be improved. On the other hand, when the content of the (D) fibrous filler is equal to or less than the upper limit (130 parts by mass), the molded article tends to have better surface appearance and excellent sliding properties. In particular, when the (D) fibrous filler is glass fiber and the content of the (D) fibrous filler is within the above range per 100 parts by mass of the (a) polyamide, the mechanical properties such as strength and rigidity, and the sliding properties of the molded product tend to be further improved.

[0071] (copper compound) The polyamide resin composition of the present embodiment may further contain a copper compound. Examples of the copper compound include, but are not limited to, copper halides, copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, copper salicylate, copper nicotinate, copper stearate, and copper complex salts coordinated with a chelating agent such as ethylenediamine or ethylenediaminetetraacetic acid. These copper compounds may be used alone or in combination of two or more.

[0072] Among these, the copper compound is preferably copper iodide, copper (I) bromide, copper (II) bromide, copper (I) chloride, or copper acetate, and more preferably copper iodide. From the viewpoint of sliding properties, the copper compound is preferably used in the form of a master batch with a halide of a metal selected from the group consisting of alkali metals and alkaline earth metals.

[0073] The content of the copper compound is 0.01 to 5 parts by mass, preferably 0.01 to 4 parts by mass, and more preferably 0.03 to 3 parts by mass, relative to 100 parts by mass of the component (A). By adjusting the blending amount of the copper compound to the above range, it is possible to improve heat aging resistance, inhibit copper precipitation and corrosion, and further to exert the effect of reducing the friction coefficient and wear depth.

[0074] (Halides of metals selected from the group consisting of alkali metals and alkaline earth metals) The polyamide resin composition of the present embodiment may further contain a halide of a metal selected from the group consisting of alkali metals and alkaline earth metals (hereinafter sometimes abbreviated as "metal halide"). Examples of the metal halide include potassium iodide, sodium iodide, potassium bromide, potassium chloride, sodium chloride, etc. Among these, potassium iodide is preferable. These metal halides may be used alone or in combination of two or more.

[0075] The amount of the metal halide to be added is 0.05 to 5 parts by mass, preferably 0.1 to 4 parts by mass, and more preferably 0.2 to 3 parts by mass, based on 100 parts by mass of the polyamide resin (A). By adjusting the blending amount of the metal halide to the above range, it is possible to improve heat aging resistance, suppress copper deposition and corrosion, and further to exert the effect of reducing the friction coefficient and wear depth.

[0076] The maximum particle size of both the copper compound and the metal halide is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less.

[0077] The particle diameter refers to the biaxial average diameter, that is, the average value of the minor axis and the major axis. Here, the minor axis and the major axis refer to the short side and the long side of the circumscribing rectangle that has the smallest area circumscribing the particle, respectively. The maximum particle diameter of the copper compound and the metal halide can be measured by observing at least 50 particles using a scanning electron microscope (SEM).

[0078] By setting the maximum particle size within the above range, the copper compound and metal halide can be finely dispersed in the polyamide resin (A) even under conditions of low moisture content in the polyamide resin (A). As a result, metal deposition and corrosion are suppressed, and the toughness, heat resistance, aging property, appearance, and color tone of the obtained polyamide resin composition are further improved. Furthermore, the friction coefficient and wear depth are reduced.

[0079] Furthermore, when the copper compound and the metal halide are made into a masterbatch, the molar ratio of halogen to copper (halogen / copper) in the masterbatch is preferably 3 to 30, more preferably 4 to 25, and even more preferably 5 to 23. By setting the molar ratio of halogen to copper to the above lower limit, copper precipitation and metal corrosion can be suppressed, while by setting the molar ratio of halogen to copper to the above upper limit, corrosion of the screw of the molding machine and the like can be suppressed without impairing mechanical properties such as toughness.

[0080] (Organic compounds having at least one amide group) In the polyamide resin composition of the present embodiment, an organic compound having at least one amide group (excluding polyamide) may be present in the masterbatch.

[0081] By including an organic compound having at least one amide group (excluding polyamides), it is possible to prevent the copper compound or metal halide from dissolving in the water in component (A) and forming a complex during melt kneading. Furthermore, it is possible to stabilize the dispersion of the copper compound or metal halide in component (A) without adversely affecting component (A), and to prevent precipitation or deterioration.

[0082] The organic compound having at least one amide group used in the present embodiment is a compound having at least one amide group in the molecular chain. Examples of the organic compound having at least one amide group include, but are not limited to, monoamides, substituted amides, methylol amides, and bisamides.

[0083] Monoamides have the general formula R-CONH 2 (wherein R is a saturated aliphatic group having 8 to 30 carbon atoms, an unsaturated aliphatic group, an aromatic group, or a group in which some of the -H groups have been replaced with -OH).

[0084] Examples of monoamides include, but are not limited to, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, oleic acid amide, erucic acid amide, linosyl acid amide, and the like.

[0085] The substituted amides are of the general formula R 1 -CONH-R 2 (However, R 1 and R 2are each independently a saturated aliphatic group, an unsaturated aliphatic group, or an aromatic group having 8 to 30 carbon atoms, or a group in which some of the -H groups have been replaced with -OH.

[0086] Examples of the substituted amides include, but are not limited to, N-lauryl lauric acid amide, N-paltimyl palmitic acid amide, N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, N-oleyl palmitic acid amide, N-stearyl 12 hydroxystearic acid amide, and N-oleyl 12 hydroxystearic acid amide.

[0087] Methylol amides have the general formula R-CONHCH 2 It is represented by OH (wherein R is a saturated aliphatic group having 8 to 30 carbon atoms, an unsaturated aliphatic group, or an aromatic group, or a group in which some of the -H groups have been replaced with -OH).

[0088] Examples of the methylol amides include methylol stearic acid amide and methylol behenic acid amide.

[0089] Bisamides have the general formula (R-CONH) 2 (CH 2 )n (wherein R is a saturated aliphatic group, an unsaturated aliphatic group, or an aromatic group having 8 to 30 carbon atoms, or a group in which some of the -H groups have been replaced with -OH; n is 1 to 8).

[0090] Examples of bisamides include, but are not limited to, methylene bislauric amide, methylene bislauric amide, methylene bishydroxystearic amide, ethylene biscaprylic amide, ethylene bislauric amide, ethylene bisstearic amide, ethylene bisisostearic amide, ethylene bishydroxystearic amide, ethylene bisbehenic amide, hexamethylene bisstearic amide, hexamethylene bisbehenic amide, and the like. amide, hexamethylene bishydroxystearic acid amide, butylene bishydroxystearic acid amide, N,N'-distearyl adipate amide, N,N'-distearyl sebacate amide, methylene bisoleate amide, ethylene bisoleate amide, ethylene biserucate amide, hexamethylene bisoleate amide, N,N'-dioleyl adipate amide, N,N'-dioleyl sebacate amide, m-xylylene bisstearic acid amide, N,N'-distearyl isophthalic acid amide, and the like.

[0091] These organic compounds having at least one amide group may be used alone or in combination of two or more kinds. Among these, bisamides are preferred.

[0092] The amount of the organic compound having at least one amide group is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5.0 parts by mass, and even more preferably 1.0 to 4.0 parts by mass, per 100 parts by mass of the polyamide resin (A). By adjusting the amount of the organic compound having at least one amide group to the above range, the dispersibility of the copper compound and metal halide in component (A) can be improved, and the heat aging resistance can be further improved. As a result, copper deposition and metal corrosion can be suppressed, and the friction coefficient and wear depth can be reduced.

[0093] The water content of the masterbatch is preferably 0.06 to 1.0 mass %, more preferably 0.10 to 0.75 mass %, and further preferably 0.15 to 0.75 mass %, based on the total mass of the masterbatch.

[0094] The moisture in the masterbatch may be present as moisture bound to the polyamide molecules, or may be moisture attached to the surface of the masterbatch, for example, the surface of the masterbatch pellets or masterbatch powder.

[0095] By controlling the moisture content within the above range, it is possible to suppress the aggregation of copper compounds and metal halides, which results in improved mechanical properties such as toughness and heat aging resistance, suppresses copper precipitation and metal corrosion, and reduces the friction coefficient and wear depth.

[0096] In the polyamide resin composition of the present embodiment, the moisture content of the masterbatch can be adjusted by controlling the degree of vacuum in the extruder, the immersion time and immersion length in the strand bath during cooling, or the amount of water sprayed.

[0097] The polyamide resin composition in this embodiment has a moisture content of preferably 0.01 to 1 mass %, more preferably 0.03 to 0.5 mass %, and further preferably 0.05 to 0.30 mass %, relative to the total mass of the polyamide resin composition.

[0098] The moisture in the polyamide resin composition may be present as moisture bound to polyamide molecules, or may be moisture attached to the surface of the polyamide resin composition, for example, the surface of pellets or powder. From the viewpoint of improving the effects of the present invention, it is more preferable that the moisture be present as moisture bound to polyamide molecules.

[0099] By controlling the moisture content of the polyamide resin composition within the above range, it is possible to suppress the aggregation of copper compounds and metal halides, which results in improved mechanical properties such as toughness and heat aging resistance, suppresses copper precipitation and metal corrosion, and reduces the friction coefficient and wear depth. The moisture content of the polyamide resin composition can be adjusted by controlling the degree of vacuum in the extruder, the immersion time and immersion length in the strand bath during cooling, or the amount of water sprayed.

[0100] (Heat stabilizer) The polyamide resin composition of the present embodiment may further contain a heat stabilizer, which is effective in improving heat aging resistance and reducing the friction coefficient and wear depth.

[0101] The heat stabilizer is not particularly limited, but examples thereof include phenol-based stabilizers such as hindered phenol compounds, phosphite-based stabilizers, hindered amine-based stabilizers, triazine-based stabilizers, and sulfur-based stabilizers. Among these, it is preferable to use a hindered phenol compound, which is a phenol-based stabilizer.

[0102] Examples of the hindered phenol compound include, but are not limited to, N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide], triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4-bis- (n-Octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2-thiobis(4-methyl-6-1-butylphenol), N,N'-hexamethionyl ethylene bis(3,5-di-tert-butyl-4-hydroxy-hydroxynamamide), 3,5-di-tert-butyl-4-hydroxy-benzyl phosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-tert-butyl-4-hydroxybenzylsulfonate calcium ethyl, tris-(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 2,6-di-tert-butyl-p-cresol, Butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-tert-butylphenol), 4,4'-thiobis-(3-methyl-6-tert-butylphenol), octylated diphenylamine, 2,4-bis[(octylthio)methyl]-o-cresol, isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol, 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane , 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-sec-triazine-2,4,6-(1H,3H,5H)trione, d-α-tocopherol, etc.

[0103] The content of the hindered phenol-based heat stabilizer is preferably 0.01 to 5 parts by mass, and more preferably 0.015 to 3 parts by mass, relative to 100 parts by mass of the component (A).

[0104] (Moldability improver) The polyamide resin composition of the present embodiment may further contain a moldability improver, if necessary, within a range that does not impair the object of the present invention. The moldability improver is not particularly limited, but examples thereof include higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, and higher fatty acid amides.

[0105] Examples of higher fatty acids include, but are not limited to, saturated or unsaturated, linear or branched aliphatic monocarboxylic acids having 8 to 40 carbon atoms, such as stearic acid, palmitic acid, behenic acid, erucic acid, oleic acid, lauric acid, and montanic acid. Of these, stearic acid and montanic acid are preferred.

[0106] The higher fatty acid metal salt is a metal salt of the above-mentioned higher fatty acid.

[0107] As the metal element of the metal salt, Groups 1, 2 and 3 of the Periodic Table, zinc, aluminum, etc. are preferred, and Groups 1 and 2 of the Periodic Table, such as calcium, sodium, potassium and magnesium, and aluminum, etc. are more preferred.

[0108] Examples of higher fatty acid metal salts include, but are not limited to, metal salts of stearic acid such as calcium stearate, aluminum stearate, zinc stearate, and magnesium stearate; metal salts of montanic acid such as calcium montanate and sodium montanate; and metal salts of palmitic acid such as calcium palmitate. Among these, metal salts of montanic acid and metal salts of stearic acid are preferred.

[0109] The higher fatty acid ester is an ester of the above-mentioned higher fatty acid and an alcohol. An ester of an aliphatic carboxylic acid having 8 to 40 carbon atoms and an aliphatic alcohol having 8 to 40 carbon atoms is preferred.

[0110] Examples of fatty alcohols include, but are not limited to, stearyl alcohol, behenyl alcohol, and lauryl alcohol.

[0111] Examples of higher fatty acid esters include stearyl stearate and behenyl behenate.

[0112] The higher fatty acid amide is an amide compound of the above-mentioned higher fatty acid.

[0113] Examples of higher fatty acid amides include, but are not limited to, stearic acid amide, oleic acid amide, erucic acid amide, ethylene bisstearylamide, ethylene bisoleylamide, N-stearylstearylamide, and N-stearylerucic acid amide.

[0114] These higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, and higher fatty acid amides may each be used alone or in combination of two or more.

[0115] (Coloring agent) The polyamide resin composition of the present embodiment may further contain a colorant, if necessary, within a range that does not impair the object of the present invention. The colorant is not particularly limited, but examples thereof include dyes such as nigrosine, pigments such as titanium oxide and carbon black, metal particles such as aluminum, colored aluminum, nickel, tin, copper, gold, silver, platinum, iron oxide, stainless steel, and titanium, and metallic pigments such as mica pearl pigments and colored graphite.

[0116] (Other resins) The polyamide resin composition of the present embodiment may further contain other resins as necessary within the scope of the present invention. Such resins are not particularly limited, but examples thereof include thermoplastic resins and rubber components described below.

[0117] Examples of thermoplastic resins include, but are not limited to, polystyrene-based resins such as atactic polystyrene, isotactic polystyrene, syndiotactic polystyrene, AS (acrylonitrile-styrene) resin, and ABS (acrylonitrile-butadiene-styrene) resin; acrylic resins such as polyacrylic acid, polyacrylic acid esters, and polymethyl methacrylate; and halogen-containing vinyl compound-based resins such as polyvinyl chloride and polyvinylidene chloride. These thermoplastic resins may be used alone or in combination of two or more.

[0118] Examples of rubber components include natural rubber, polybutadiene, polyisoprene, polyisobutylene, neoprene, polysulfide rubber, thiokol rubber, acrylic rubber, urethane rubber, silicone rubber, epichlorohydrin rubber, styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butadiene random copolymer, hydrogenated styrene-butadiene random copolymer, styrene-ethylene-propylene random copolymer, Examples of the core-shell type rubber include styrene-ethylene-butylene random copolymers, ethylene-propylene copolymers (EPR), ethylene-(1-butene) copolymers, ethylene-(1-hexene) copolymers, ethylene-(1-octene) copolymers, ethylene-propylene-diene copolymers (EPDM), butadiene-acrylonitrile-styrene-core-shell rubber (ABS), methyl methacrylate-butadiene-styrene-core-shell rubber (MBS), methyl methacrylate-butyl acrylate-styrene-core-shell rubber (MAS), octyl acrylate-butadiene-styrene-core-shell rubber (MABS), alkyl acrylate-butadiene-acrylonitrile-styrene core-shell rubber (AABS), butadiene-styrene-core-shell rubber (SBR), and siloxane-containing core-shell rubbers such as methyl methacrylate-butyl acrylate siloxane. These rubber components may be used alone or in combination of two or more.

[0119] The polyamide resin composition of the present embodiment is not particularly limited as long as it is used for applications requiring mechanical properties and sliding properties, and can be widely used as a raw material for sliding parts such as electric and electronic parts, automobile parts, building parts, industrial parts, etc. Examples of sliding parts include bearings, gears, door checkers, chain guide parts, etc., which are generally used as injection molded articles.

[0120] <Method of producing polyamide resin composition> The polyamide resin composition of the present embodiment can be obtained by mixing and kneading (A) a polyamide resin, (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer in its side chain, (C) a compatibilizer, (D) a fibrous filler, and other components such as a copper compound and a metal halide, as necessary.

[0121] The copper compound and the metal halide are preferably made into a master batch in advance and then melt-kneaded with the components (A), (B), and (C). Alternatively, the copper compound, the metal halide, and the component (A) are preferably made into a master batch in advance and then melt-kneaded with the components (B) and (C). In addition, during the production of the polyamide resin composition, the raw material of component (C) can be added when mixing and kneading component (A) with a copper compound and a metal halide that are added as necessary, and other components, thereby preparing the polyamide resin composition in a twin-screw extruder.

[0122] (Masterbatch preparation process) The master batch is prepared by melt-kneading the copper compound and the metal halide. In addition to the copper compound and metal halide, it is preferable to incorporate the organic compound having at least one amide group (excluding polyamide). It is preferable to incorporate component (A) in addition to an organic compound having at least one amide group (excluding polyamides).

[0123] When an organic compound having at least one amide group (excluding polyamide) is mixed with the component (A), the copper compound, the metal halide, and the organic compound having at least one amide group (excluding polyamide) may be mixed alone in the component (A). Also, at least two of the three types of compounds may be mixed in advance and then mixed in the component (A), or at least two of the three types of compounds may be mixed in advance and crushed and then mixed in the component (A), or at least two of the three types of compounds may be mixed in advance and crushed to form a tablet and then mixed in the component (A).

[0124] The compounds can be mixed by any known method, for example, by using a tumbler, a Henschel mixer, a Plosser mixer, a Nauta mixer, a flow jet mixer, or the like.

[0125] A known method can be used to pulverize the compound. For example, a method using any one of a hammer mill, a knife mill, a ball mill, a jaw crusher, a cone crusher, a roller mill, a jet mill, and a mortar can be used to pulverize the compound.

[0126] A known method can be used to make a compound into a tablet form, such as a compression granulation method, a tablet molding method, a dry extrusion granulation method, or a melt extrusion granulation method.

[0127] The melt-kneading device is not particularly limited, and known devices can be used. As the melt-kneading device, for example, a single-screw or twin-screw extruder, a Banbury mixer, a mixing roll, or other melt-kneading device is preferably used. Among them, a twin-screw extruder is preferably used. The melt-kneading device may be equipped with a degassing mechanism (vent) device and a side feeder device.

[0128] The melt-kneading temperature in this embodiment is preferably in the range of 1°C higher than the melting point or softening point of component (A) determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121 to 310°C, more preferably in the range of 10°C higher to 300°C, and even more preferably in the range of 15°C higher to 295°C. In this embodiment, the melt-kneading temperature is the barrel setting temperature of the extruder. The shear rate in the kneader is 100 (SEC -1 The average residence time during kneading is preferably about 0.5 to 15 minutes.

[0129] (Melt-kneading process of master batch, component (A), component (B), and component (C)) The polyamide resin composition of the present embodiment is produced by melt-kneading the master batch, the (A), (B) and (C) components. When the (A) component is blended in the master batch, the polyamide resin composition of the present embodiment is prepared by melt-kneading the (B) and (C) components with the master batch.

[0130] The copper compound and metal halide are preferably mixed in a ratio of 0.1 to 100 parts by mass, more preferably 0.1 to 20 parts by mass, in total relative to 100 parts by mass of the (A) polyamide resin.

[0131] By setting the total mass of the copper compound and the metal halide within the above range, metallic copper precipitation and metal corrosion in an extruder or a molding machine are suppressed, and stability during processing is improved. As a result, the heat aging resistance is further improved, the friction coefficient and wear depth are further reduced, and the change in appearance color due to water absorption can be further suppressed without deteriorating the mechanical properties of the product.

[0132] The blending ratio of the components (B) and (C) relative to 100 mass % of the polyamide resin (A) is as described above.

[0133] The master batch, component (A), component (B), and component (C) are melt-kneaded together with other components which are blended as necessary.

[0134] The melt-kneading step is preferably carried out using various commonly used extruders such as a single-screw or twin-screw extruder. From the viewpoints of productivity, versatility, etc., it is particularly preferable to carry out the step using a twin-screw extruder. In this case, the melt-kneading temperature, which depends on the type of component (A), is preferably adjusted to a temperature at which the temperature of the molten resin discharged from the extruder outlet is equal to or higher than the melting points of components (A), (B), and (C).

[0135] By setting the melt kneading temperature within the above range, poor extrusion kneading is unlikely to occur, and the components (B) and (C) can be finely dispersed.

[0136] In the case of a twin-screw extruder, it is preferable that the extruder screw has a kneading zone that combines at least two kneading disks. The kneading zone is a region that applies high shear while suppressing the progress of the molten resin in the extrusion direction so that kneading is performed effectively.

[0137] In the melt-kneading step, the (A) component, the (B) component, the (C) component, and the master batch (copper compound and metal halide), as well as other components (hindered phenol-based heat stabilizer, etc.) are fed from the most upstream feed port of the twin-screw extruder, and melt-kneaded in the first kneading zone to obtain a first melt-kneaded product. Furthermore, if necessary, a (D) fibrous filler is fed from a side feed port provided downstream of the first kneading zone, and the non-melted (D) fibrous filler is dispersed in the first melt-kneaded product in the second kneading zone provided downstream of the side feed port.

[0138] It is desirable to set the various conditions of the extruder (barrel temperature, screw rotation speed, discharge amount, etc.) so that the resin temperature of the polyamide resin composition discharged from the extruder outlet after the melt-kneading step is higher than the crystallization temperature of the (A) component and is 280°C to 400°C. By setting the temperature of the polyamide resin composition at the outlet to 280°C to 400°C, the (A), (B) and (C) components can be more finely dispersed. As a result, a polyamide resin composition having excellent sliding properties and mechanical properties can be obtained.

[0139] The temperature of the polyamide resin composition is preferably measured, for example, by directly contacting the detection part of a commercially available thermocouple thermometer with the molten polyamide resin composition discharged from the outlet of an extruder. The temperature of the extruder for achieving the above-mentioned temperature of the polyamide resin composition is preferably set to 280°C or higher and 400°C or lower.

[0140] By molding the polyamide resin composition, a molded article of the polyamide resin composition of the present embodiment can be obtained. The method for obtaining the molded product is not particularly limited, and any known molding method can be used. Examples of molding methods include extrusion molding, injection molding, vacuum molding, blow molding, injection compression molding, decorative molding, other material molding, gas-assisted injection molding, foam injection molding, low-pressure molding, ultra-thin-wall injection molding (ultra-high-speed injection molding), and in-mold composite molding (insert molding, outsert molding), etc.

[0141] The temperature setting of the molding machine when molding the polyamide resin composition of this embodiment is preferably in the range of from 5°C higher than the melting point of the (A) component used to 310°C, more preferably from 10°C higher to 300°C, and even more preferably from 15°C higher to 295°C.

[0142] By setting the temperature of the molding machine within the above temperature range, the polyamide resin composition can be effectively kneaded during molding, and the components (B) and (C) in the polyamide resin composition can be more finely dispersed.

[0143] The polyamide resin composition of the present invention can be widely used as a raw material for sliding parts such as electric / electronic parts, automobile parts, building parts, industrial parts, etc., as long as the application requires mechanical properties and sliding properties, and is not particularly limited. Examples of the sliding parts include generally injection molded products such as bearings, gears, door checkers, chain guides, and roller parts. EXAMPLES

[0144] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.

[0145] [Production Example] (Production Example 1) Preparation of Polyamide 66 15000g of an equimolar salt of adipic acid and hexamethylenediamine, and 0.5 mol% excess adipic acid relative to the total equimolar salt components were dissolved in 15000g of distilled water to obtain a 50% by mass aqueous solution of the raw material monomer. The obtained aqueous solution was placed in an autoclave with an internal volume of 40L, and the inside of the autoclave was replaced with nitrogen. This aqueous solution was stirred at a temperature of 110 to 150°C, and the water vapor was gradually removed to concentrate the solution concentration to 70% by mass. Thereafter, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. The reaction was continued for 1 hour while gradually removing water vapor and maintaining the pressure at 1.8 MPa until the internal temperature reached 270°C. The pressure was then reduced to atmospheric pressure over about 1 hour, and after atmospheric pressure was reached, the mixture was discharged in the form of strands from the lower nozzle, water-cooled and cut to obtain pellets. The pellets obtained were dried in a nitrogen stream at 90°C for 4 hours. The pellets had a relative viscosity of 2.71 in 98% sulfuric acid, a melting point of 265°C, and a crystallization temperature of 220°C.

[0146] ((A) Polyamide resin) (A-1) Polyamide resin (A-2) Polyamide resin: 1200-321, manufactured by Asahi Kasei Corporation (A-3) Polyamide resin: 1500-X31, manufactured by Asahi Kasei Corporation (A-4) Polyamide resin: 1700-X11, manufactured by Asahi Kasei Corporation (A-5) Polyamide resin: 3100-X11, manufactured by Asahi Kasei Corporation (A-6) Polyamide resin: Stanyl TW341-J, manufactured by DSM Co., Ltd. (A-7) Polyamide resin: SF1013A, manufactured by UBE Corporation (A-8) Polyamide resin (described in Production Example 4)

[0147] ((B) Polyolefin-based graft copolymer having aromatic ring-containing polymer in the side chain) (B-1): MODIPER-A1100, NOF Corporation, polyolefin graft copolymer (B-2): MODIPER-A1401, NOF Corporation, polyolefin graft copolymer (B'-1): ENGAGE 8180: Ethylene-octene copolymer, manufactured by Dow Chemical Japan Co., Ltd.

[0148] ((C) Compatibilizer) (C-1-1) APOLHYA LP91: Manufactured by Arkema Co., Ltd., polyolefin-polyamide polymer (C-1-2) Graft copolymer (described in Production Example 3): polystyrene-polyamide polymer (C-2-1) FUSABOND N525: Maleic anhydride modified polyolefin polymer manufactured by Dow Chemical Co. (C-2-2) FUSABOND MN493D: Maleic anhydride modified polyolefin polymer manufactured by The Dow Chemical Company (C-2-3) FUSABOND N416: Dow Chemical Company, maleic anhydride modified polyolefin polymer (C-2-4) Tuftec M1943: Asahi Kasei Corporation, styrene-based thermoplastic elastomer (C-3-1) XIBOND 180: Styrene-maleic anhydride copolymer manufactured by Polyscope (C-3-2) XIBOND 120: Styrene-maleic anhydride copolymer manufactured by Polyscope (C-3-3) XIBOND 280: Styrene-maleic anhydride copolymer manufactured by Polyscope (C-3-4) Maleic anhydride modified polyphenylene ether (m-PPE) (Asahi Kasei) (molecular weight: 54,000)

[0149] (D) Fibrous filler (D-1) Glass fiber (manufactured by Nippon Electric Glass, product name "ECS03T275H", average fiber diameter 10 μm, cut length 3 mm) (D-2) Glass fiber (manufactured by Nippon Electric Glass, product name "ECS03T289DE", average fiber diameter 7 μm, cut length 3 mm) (D-3) Glass fiber (manufactured by Nitto Boseki, product name "CS-3DE-456S", average fiber diameter 7 μm, cut length 3 mm) (D-3) Carbon fiber (Teijin, product name "HTC413") (D-4) Carbon fiber (Teijin, product name "IMP303") (D-5) Carbon fiber (Teijin, product name "HTM100") (D-6) Aramid fiber (manufactured by Teijin, product name "TECHNORA T322EH")

[0150] (Other ingredients) Copper iodide: Copper(I) iodide, manufactured by Wako Pure Chemical Industries, Ltd. Potassium iodide: Potassium iodide, manufactured by Wako Pure Chemical Industries, Ltd. Hindered phenolic heat stabilizer: BASF, IRGANOX1098 Spreader: Sanyo Chemical Industries, Ltd., PEG400 Azine dyes: Nigrosine, NUBIAN(R) BLACK TH-807 manufactured by Orient Chemical Industries Co., Ltd.

[0151] (Production Example 2) Preparation of Masterbatch To 100 parts by mass of the polyamide resin (A-1) obtained in the above (Production Example 1), 1.5 parts by mass of a copper compound and 32.5 parts by mass of a 40% by mass aqueous solution of a metal halide were added. Using a twin-screw extruder (manufactured by the Institute of Plastics Engineering, twin-screw rotating in the same direction, L / D=60 (D=30φ)), the mixture was melt-kneaded at a screw rotation speed of 100 rpm and a cylinder temperature of 280°C to obtain a master batch containing the polyamide resin (A-1), the copper compound, and the metal halide.

[0152] (Production Example 3) Preparation of polystyrene-polyamide polymer 10% by weight of compatibilizer (C-3-1) was added to polyamide resin (A), and the mixture was melt-kneaded using a twin-screw extruder (manufactured by the Institute of Plastics Engineering, twin-screw co-rotating type, L / D=60 (D=30φ)) at a screw rotation speed of 300 rpm and a cylinder temperature of 280°C to obtain a polystyrene-polyamide polymer containing polyamide resin (A) and 10% by weight of compatibilizer (C-3-1).

[0153] (Production Example 4) Preparation of crystalline semi-aromatic polyamide resin A 50 liter tumble dryer was charged with 15 kg of 4T / 6T salt (39 / 61 mol / mol). The tumble dryer was evacuated to 50 mbar and backfilled with nitrogen, which was repeated five times. The mixture was heated to a temperature of 220° C. in 5 hours, then to 255° C. in 15 hours, while the reaction water was leaving the tumble dryer. A low nitrogen purge was used during the reaction. The mixture was cooled to 235° C. in 19 hours, and a mixture of 650 kg of 1,6-hexamethylenediamine, 300 g of 1,4-butanediamine, and 1.0 kg of water was added over 7 hours, while maintaining the temperature at 235° C. The mixture was allowed to react at 235° C. for an additional 29 hours. The nitrogen flow was then increased, and the material was cooled to room temperature. A white powder was obtained.

[0154] [Example 1] (A-1) polyamide resin, (B-1) polyolefin graft copolymer, and (C-1-1) compatibilizer were mixed in the amounts shown in Table 1 and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") with a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 290°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, (D-1) fibrous filler was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of a polyamide resin composition at a discharge rate of 25 kg / h. The obtained pellets of the polyamide resin composition were molded into a multipurpose test piece type A in accordance with ISO 3167 using an injection molding machine NEX50IV-5EG (manufactured by Nissei Plastics Co., Ltd., screw diameter 26 mm, injection volume 49 cm3) with the following settings: injection + pressure holding time 25 seconds, cooling time 15 seconds, mold temperature 80°C, cylinder temperature = (same as the barrel temperature of the extruder).

[0155] [Examples 2 to 20] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the amounts were increased and / or decreased as shown in Table 1 and / or Table 3.

[0156] [Example 21] As shown in Table 3, instead of the polyamide resin (A-1), the polyamide resin (A-4) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 300°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of the polyamide resin composition at a discharge rate of 20 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the pellets were obtained.

[0157] [Example 22] Pellets of the polyamide resin composition were prepared in the same manner as in Example 1. 10 kg of the obtained pellets were placed in a conical ribbon vacuum dryer (manufactured by Okawara Manufacturing Co., Ltd., product name Ribocone RM-10V) and thoroughly substituted with nitrogen. The pellets were heated at 190°C for 6 hours while stirring and flowing nitrogen at 1 L / min. After that, the temperature was lowered while still flowing nitrogen, and when the temperature reached about 50°C, the pellets were removed from the apparatus. The resulting pellets and test pieces were prepared.

[0158] [Example 23] As shown in Table 4, instead of the polyamide resin (A-1), the polyamide resin (A-6) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 310°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port at a discharge rate of 25 kg / h to prepare pellets and test pieces of the polyamide resin composition.

[0159] [Example 24] As shown in Table 4, instead of the polyamide resin (A-1), the polyamide resin (A-7) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 260°C, and the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port while melt-kneading at a screw rotation speed of 300 rpm, and pellets of the polyamide resin composition were obtained at a discharge rate of 25 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the pellets were obtained by extruding the fibrous filler (D-1) from a side feed port provided downstream of the most upstream feed port while melt-kneading at a screw rotation speed of 300 rpm.

[0160] [Example 25] As shown in Table 4, instead of the polyamide resin (A-1), the polyamide resin (A-5) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 250°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of the polyamide resin composition at a discharge rate of 25 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the pellets were obtained.

[0161] [Example 26] As shown in Table 4, instead of the polyamide resin (A-1), the polyamide resin (A-5) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 340°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of the polyamide resin composition at a discharge rate of 25 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the pellets were obtained.

[0162] [Example 27] As shown in Table 4, in addition to the polyamide resin (A-3), 43 parts by mass of the polyamide resin (A-1) were blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 300°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-2) was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of the polyamide resin composition at a discharge rate of 25 kg / h. Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the temperature of the barrel of the extruder was set to 300°C, and the mixture was melt-kneaded at a screw rotation speed of 300 rpm.

[0163] [Example 28] As shown in Table 4, in addition to the polyamide resin (A-1), 43 parts by mass of the polyamide resin (A-8) were blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 320°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port, to obtain pellets of the polyamide resin composition at a discharge rate of 25 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the pellets were obtained.

[0164] [Examples 29 to 36] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the compatibilizer (C) was added in an increased and / or decreased amount as shown in Tables 4 to 6 instead of the compatibilizer (C-1-1).

[0165] [Example 37] As shown in Table 6, in addition to the polyamide resin (A-1), 2 parts by mass of the master batch obtained in (Production Example 2) was blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 290°C, and while melt-kneading was performed at a screw rotation speed of 300 rpm, the fibrous filler (D-1) was fed and extruded from a side feed port provided downstream of the most upstream feed port, and pellets of the polyamide resin composition were obtained at a discharge rate of 25 kg / h in the same manner as in Example 1, except that, and evaluation was performed.

[0166] [Example 38] As shown in Table 6, in addition to the polyamide resin (A-1), 2 parts by mass of the master batch obtained in (Production Example 2), 0.05 parts by mass of a hindered phenol-based heat stabilizer: IRGANOX1098 manufactured by BASF, 0.02 parts by mass of a spreading agent: PEG400 manufactured by Sanyo Chemical Industries, Ltd., and 0.005 parts by mass of an azine-based dye Nigrosine: NUBIAN (registered trademark) BLACK TH-807 manufactured by Orient Chemical Industry Co., Ltd. were blended and fed from the most upstream feed port of a twin-screw extruder (manufactured by Coperion Co., Ltd., product name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 290 ° C., and while melt-kneading at a screw rotation speed of 300 rpm, (D-1) a fibrous filler was fed and extruded from a side feed port provided downstream of the most upstream feed port, and pellets of the polyamide resin composition were obtained at a discharge rate of 25 kg / h. The pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1.

[0167] [Comparative Example 1] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the (C) compatibilizer and the (D) fibrous filler were not blended and the (B-1) polyolefin graft copolymer was blended as shown in Table 6.

[0168] [Comparative Example 2] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that the compatibilizer (C) was not blended and the polyolefin graft copolymer (B-1) was blended as shown in Table 5.

[0169] [Comparative Example 3] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B'-1) polyolefin copolymer was blended as shown in Table 6 instead of (B) polyolefin graft copolymer.

[0170] [Comparative Example 4] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B) polyolefin-based graft copolymer was not blended and was blended as shown in Table 6.

[0171] [Comparative Example 5] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B) polyolefin-based graft copolymer was not blended and was blended as shown in Table 7.

[0172] [Comparative Example 6] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B) polyolefin-based graft copolymer was not blended and was blended as shown in Table 7.

[0173] [Comparative Example 7] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B) the polyolefin graft copolymer and (C) the compatibilizer were not blended and were blended as shown in Table 7.

[0174] [Comparative Example 8] Pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1, except that (B) the polyolefin graft copolymer and (C) the compatibilizer were not blended and were blended as shown in Table 7.

[0175] <Evaluation> The test pieces prepared in each of the Examples and Comparative Examples were used to carry out the following evaluations.

[0176] (Reciprocating sliding test) Using the multipurpose test piece A obtained in the examples and comparative examples, a sliding test was performed with a pin-on-disk tribometer (TRB3 model manufactured by Anton Paar) using a SUS304 test piece (a ball with a diameter of 6.5 mm) as the counter material at a linear velocity of 50 mm / sec, a reciprocating distance of 20 mm, a temperature of 23°C, and a humidity of 50%. Furthermore, a friction coefficient test was performed with a load of 4 kg and 10,000 reciprocating cycles. In addition, the maximum wear depth (μm) of the wear marks on the samples after the sliding test was measured with a surface roughness meter (575A-30 manufactured by Toyo Seimitsu Co., Ltd.). The friction coefficient and wear depth were measured using the above-mentioned test, and the results are shown in Table 1. In the evaluation of the wear of the mating material, the surface (sliding surface) of the mating material SUS304 test piece after the reciprocating sliding test was observed using a digital microscope (Keyence VHX-5000 type) at a magnification of 20 times. The observation results of the mating material were evaluated on a scale of 1 to 5 as follows, and the results are shown in Table 1. 1: Large amounts of wear are observed on the mating material. 2: Scraping is observed on the mating material. 3: Some wear is observed on the mating material. 4: Slight chipping of the mating material is observed. 5: Almost no wear of the mating material is observed.

[0177] (Limit PV test) Using the multipurpose test specimens A-type obtained in the examples and comparative examples, a friction and wear tester (EFM-III-F type manufactured by A&D Co., Ltd.) was used, and a S45C ring (surface roughness 0.8 μmRa / contact area approximately 2 square centimeters) was used as the mating material. A sliding test was performed at a rotation speed of 0.5 m / sec, a temperature of 23 °C, and a humidity of 50%. The test was started with an initial load of 40 N, and the load was increased by 50 N every 10 minutes. A flat plate measuring 30 mm x 2 mm in length and width was used as the test specimen. The limit point at which the flat plate of the test specimen was worn down by 1.5 mm due to the melting of the sample or the increase in the amount of wear in the above test was calculated as the limit PV value (kPa m / s). The obtained limit PV value was then evaluated on a scale of 1 to 5 as shown below, and the results are shown in Table 1. 1: Less than 600 kPa m / s 2: 600 kPa m / s or more, less than 800 kPa m / s 3: 800 kPa m / s or more, less than 1000 kPa m / s 4: 1000 kPa m / s or more, less than 1200 kPa m / s 5:1200kPa m / s or more

[0178] (Tensile test) Using the multipurpose test pieces A obtained in the examples and comparative examples, tensile tests were carried out at a test speed of 50 mm / min in accordance with ISO 527 to measure the tensile strength (N / mm). The measurement results are shown in Table 1. The ratio of the amount of displacement of the chuck distance at break to the chuck distance before the test was defined as the tensile elongation (%). Tensile elongation (%) = 100 x breaking point displacement (mm) / initial chuck distance (mm) The tensile strength was divided by the tensile elongation to calculate the tensile modulus (MPa). The calculation results are shown in Table 1. Tensile modulus = tensile strength / tensile elongation

[0179] (Charpy impact strength) The multipurpose test specimens A obtained in the examples and comparative examples were processed to 80 x 10 x 4 mm, and the notched Charpy impact strength (kJ / m 2 ) was measured.

[0180] [Table 1]

[0181] [Table 2]

[0182] [Table 3]

[0183] [Table 4]

[0184] [Table 5]

[0185] [Table 6]

[0186] [Table 7]

[0187] From the results of Tables 1 to 7, the polyamide resin compositions of each Example were excellent in all of the sliding properties (friction coefficient, wear depth, mating material wear, limit PV value) and mechanical properties (tensile strength, elastic modulus, impact resistance). Among them, it was confirmed that the limit PV value was improved while reducing the mating material wear after the reciprocating sliding test by combining the (B) and (C) components with the (D) component, compared with the comparative example. Furthermore, from the results of Examples 19 to 28, it was found that the combination of the (B) and (C) components with the (D) component resulted in excellent sliding properties and mechanical properties in all cases, without being limited to the type of polyamide resin (A). Furthermore, from the results of Examples 8, 9, 14 to 18, and 29 to 36, it was found that the combination of the (B) and (C) components with the (D) component resulted in excellent sliding properties and mechanical properties in various combinations, without being limited to or dependent on each component being one type.

[0188] On the other hand, from the results of Tables 1 to 7, the polyamide resin compositions of the comparative examples, which are excellent in some properties, were obtained, but the sliding properties and mechanical properties were inferior. In particular, the sliding properties were significantly inferior compared to the examples. Furthermore, in Comparative Examples 1 and 2, which did not contain the (C) component, all properties were inferior, and in terms of moldability, when injection molding was performed, the molten resin leaked from the nozzle tip of the injection molding machine, making continuous injection molding difficult, resulting in low industrial applicability. Furthermore, in Comparative Examples 3 to 7, which did not contain the (B) component, the sliding properties were significantly inferior. [Industrial Applicability]

[0189] The polyamide resin composition of the present invention has excellent sliding properties and mechanical properties, and therefore has potential applications in the fields of automobiles, electricity and electronics, machinery and industry, office equipment, aviation and space, etc. In addition, by combining components (B), (C), and (D), each component can exhibit its performance without being limited to or dependent on one type. Furthermore, a wide range of combinations are possible, and the composition has potential applications in a wide range of industries.

Claims

1. (A) a polyamide resin; (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain; (C) a compatibilizer; and (D) a fibrous filler; and A polyamide resin composition comprising:

2. The polyamide resin composition according to claim 1, wherein the compatibilizer (C) has an olefin skeleton and / or an aromatic ring skeleton.

3. The polyamide resin composition according to claim 1 or 2, characterized in that the content of the polyolefin graft copolymer (B) is 1 to 15 parts by mass relative to 100 parts by mass of the polyamide resin (A), the content of the compatibilizer (C) is 0.01 to 15 parts by mass relative to 100 parts by mass of the polyamide resin (A), and the content of the fibrous filler (D) is 1 to 150 parts by mass relative to 100 parts by mass of the polyamide resin (A).

4. The polyamide resin composition according to claim 1 or 2, wherein the compatibilizer (C) has affinity for an olefin skeleton.

5. The polyamide resin composition according to claim 1 or 2, wherein the compatibilizer (C) has affinity for an aromatic ring.

6. 3. The polyamide resin composition according to claim 1, wherein the compatibilizer (C) has a functional group reactive with the polyamide resin (A).

7. 3. The polyamide resin composition according to claim 1, wherein the polyolefin graft copolymer (B) has a polyethylene main chain.

8. The polyamide resin composition according to claim 1 or 2, wherein the compatibilizer (C) contains a structural unit derived from a carboxylic acid anhydride.

9. 3. The polyamide resin composition according to claim 1, wherein the fibrous filler (D) has a ratio (L / d1) of an average major axis L to an average minor axis d1 of 1,000 or less.

10. 3. The polyamide resin composition according to claim 1, wherein the compatibilizer (C) has an amide bond in a side chain.

11. A method for producing a polyamide resin composition, comprising melt-kneading (A) a polyamide resin, (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in its side chain, and (C) a compatibilizer.

12. A molded article, which is obtained by molding the polyamide resin composition according to claim 1 or 2.

13. A sliding member comprising the polyamide resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Slide member for power transmission guide

    JP2011084679A

  • Polyamide resin composition, its molding, and method for using the same

    JP2012102189A

  • Polyamide resin composition and resin molded article thereof

    JP2016117842A

  • Resin composition and sliding member using same

    WO2013047625A1